PENDIDIKAN KARAKTER DI ERA DIGITAL: MENJAGA MORALITAS DI TENGAH PERUBAHAN ZAMAN - Adhisti Adinda Putri; Muhammad Jufri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of technology in the digital era has brought transformative changes to societal lifestyles, particularly in communication and learning. While offering numerous benefits, these advancements present significant challenges to the character and morality of the younger generation, who are increasingly vulnerable to issues such as cyberbullying, hoaxes, and non-educational content. Consequently, character education has become a fundamental necessity to preserve moral integrity amidst these shifts. This research aims to provide a comprehensive foundation and guidelines for society to navigate digital challenges while offering strategic insights into maintaining morality through character strengthening. ​Utilizing a qualitative approach with a library research design, this study examines relevant sources concerning the impact of the digital era on education. The analysis focuses on three primary pillars: the optimization of digital literacy, the strategic role of the family unit, and the integration of religious values in shaping resilient character. The results of the literature review demonstrate that synergy between digital literacy, ethics-based character development, and proactive family supervision plays a crucial role in safeguarding the morality of the younger generation. Ultimately, the study concludes that utilizing technology productively and responsibly serves as a vital solution to fostering moral awareness in the digital age.